﻿Le frontispice de la Pompe funèbre du duc Charles III : pensée figurée et imaginaire matériel à la cour de Lorraine au début du XVIIe siècle - Choné, Paulette (RACAR : Revue d'art canadienne / Canadian Art Review, 1988)
The symbolic system of power in the Duchy of Lorraine, an independent state, consolidated itself during the long reign of Charles iii (1545-1608). The prince’s political actions and his virtues are celebrated in a set of 74 engravings describing the 40 days of mourning that brought together representatives from all the courts of Europe. The plates reflect the solemn attitudes of the court of France, but the main influence of the engravings can be linked to Germanic, Dutch, and Italian traditions. To find the symbolism of mourning, it is necessary to look beyond the traditional ceremonial pattern to the frontispiece of the souvenir collection and the funeral prayer of the duke. A link can be found between the rhetoric of the prayer and the means of expression in the frontispiece. Secretary Claude de La Ruelle is credited with having initiated this great collection of plates. He was probably assisted in the decorative program of the frontispiece by Father Léonard Périn, a Jesuit from the University of Pont-à-Mousson, who led the funeral prayer. La Ruelle commissioned the engravings of Frédéric Brentel, accompanied by Matthieu Merian who signed the frontispiece. Although the frontispiece has been carefully described by Pierre Marot, he did not include a detailed account of its symbolic function. Given the cultural passion for symbolism in the region to which the Duchy of Lorraine belonged and the intellectual pursuits of Jesuits combined with the “culture de la curiosité,” fashionable in the French court and artistic circles alike, a more detailed reading of the iconography of the frontispiece is needed.The similarity between the structure of the frontispiece and a marquetry cabinet can only be hypothetical. The whole may be seen as a microcosm of Lorraine’s hierarchical setting, uniting the naturalistic cause and the allegorical teachings. The symbolic expression, although discreet, plays a role in accentuating the senses by bringing out a more pronounced meaning at a higher level of interpretation. The source of these figurative thoughts from the frontispiece should not be attributed to Ripa’s Iconologia, but rather to the equally famous works of Valeriano, known by the learned community of Nancy. Hieroglyphica are not the only source for this work, which is linked to a culture where elegantly conceived symbols dominate the teachings and documentation of events. The most captivating characteristic is without a doubt its successful synthesis of conceptual imagery and imaginative material taken from the rarest gifts of nature.